1988
DOI: 10.1073/pnas.85.24.9552
|View full text |Cite
|
Sign up to set email alerts
|

Terminal differentiation and calcification in rabbit chondrocyte cultures grown in centrifuge tubes: regulation by transforming growth factor beta and serum factors.

Abstract: Rabbit chondrocyte cultures on plastic dishes are capable of depositing a cartilaginous matrix, although the matrix does not calcify unless high levels of phosphate are added to the medium. In the present study, we cultivated a pelleted mass of, rabbit growth-plate chondrocytes in the presence of Eagle's minimum essential medium supplemented with 10% fetal bovine serum and 50 ,sg of ascorbic acid per ml in a plastic centrifuge tube. These cells proliferated for several generations and then reorganized into a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
158
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(168 citation statements)
references
References 24 publications
(36 reference statements)
8
158
2
Order By: Relevance
“…The cell system employed in the present study consists of an SV-40 immortalized human osteoblastic cell line (SV-HFO) [23] that undergo differentiation as evidenced by mineralization, upon treatment with dexamethasone [25]. Our results demonstrating that TGF-fl~ inhibits alkaline phosphatase expression and mineralization are consistent with several previous studies showing that TGF-fll appears to be an inhibitor of bone nodule formation and mineralization in osteoblast cultures [8][9][10]13,37]. A number of in vivo models have been established and it has been repeatedly shown that TGF-fl injections stimulated bone formation [4][5][6][7].…”
Section: K Iba Et Al/febs Letters 373 (1995) 1~1supporting
confidence: 87%
“…The cell system employed in the present study consists of an SV-40 immortalized human osteoblastic cell line (SV-HFO) [23] that undergo differentiation as evidenced by mineralization, upon treatment with dexamethasone [25]. Our results demonstrating that TGF-fl~ inhibits alkaline phosphatase expression and mineralization are consistent with several previous studies showing that TGF-fll appears to be an inhibitor of bone nodule formation and mineralization in osteoblast cultures [8][9][10]13,37]. A number of in vivo models have been established and it has been repeatedly shown that TGF-fl injections stimulated bone formation [4][5][6][7].…”
Section: K Iba Et Al/febs Letters 373 (1995) 1~1supporting
confidence: 87%
“…The process of bone formation through endochondral ossification means that bone forms by replacing a cartilage anlagen after the chondrocytes undergo a process of hypertrophy, calcification, and apoptosis known as chondrocyte terminal differentiation. It has been shown that TGF-β1 inhibits the terminal differentiation of chondrocytes and that TGF-β1 acts to preserve the chondrocyte phenotype [45,46]. Our results suggest that sustained administration of TGF-β1 may be more effective in suppressing terminal differentiation than intermittent dosing.…”
Section: Discussionmentioning
confidence: 59%
“…[15][16][17] The chondrogenic potential of human mesenchymal stem cells (hMSC) is well described. 18,19 Addition of transforming growth factor-beta-1 (TGF-b1) to hMSC has been shown to consistently induce chondrogenesis while avoiding terminal differentiation [20][21][22][23][24] Adenoviral mediated transfer of TGF-b1 genes to hMSC has been shown to similarly induce chondrogenesis and inhibit terminal differentiation. 21 Efficient and sustained gene delivery to mesenchymal stem cells with adenovirus, lentivirus and retrovirus have been described.…”
Section: Introductionmentioning
confidence: 99%